2013
DOI: 10.1155/2013/853475
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anti-Inflammatory and Antimicrobial Herbal Remedy PADMA 28 on Immunological Angiogenesis and Granulocytes Activity in Mice

Abstract: PADMA 28 is a herbal multicompound remedy that originates from traditional Tibetan medicine and possesses anti-inflammatory, antioxidant, antimicrobial, angioprotecting, and wound healing properties. The aim of the present study was to evaluate the influence of this remedy on immunological angiogenesis and granulocytes metabolic activity in Balb/c mice. Mice were fed daily, for seven days, with 5.8 mg of PADMA (calculated from recommended human daily dose) or 0.085 mg (dose in the range of active doses of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Two cellular studies on cardamom demonstrated the suppression and inhibition of IL-6 and TNF-α release [ 62 , 63 ]. The beneficial effects of cardamom on inflammatory factors including IL-6, TNF-α, and NF-κB [ 64 66 ] and serum AST and ALT levels [ 66 71 ] had been observed in most of the animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Two cellular studies on cardamom demonstrated the suppression and inhibition of IL-6 and TNF-α release [ 62 , 63 ]. The beneficial effects of cardamom on inflammatory factors including IL-6, TNF-α, and NF-κB [ 64 66 ] and serum AST and ALT levels [ 66 71 ] had been observed in most of the animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue vascularity is a crucial factor for the healing process since it provides oxygen and nutrients for cells' metabolic activity [ 7 , 39 , 40 ]. Our results showed that rats receiving high-fat diet and alcohol had a lower vascularization and therefore a delay in wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…In our research [ 36 ], PADMA 28 was administered to mice per os , at a dose of 5.8 mg and 0.085 mg/day/mouse, in 40 μl of water for 7 days, while animals from control groups received 40 μl of water. Then, mice were bled under anesthesia, sacrificed, and spleens were harvested.…”
Section: Angiogenesis Regulation By Some Natural Antioxidantsmentioning
confidence: 99%